2023
DOI: 10.1101/2023.12.25.23300515
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbiota based personalized nutrition improves hyperglycaemia and hypertension parameters and reduces inflammation: A prospective, open label, controlled, randomized, comparative, proof of concept study

Gopalakrishna Kallapura,
Anthony Surya Prakash,
Kumar Sankaran
et al.

Abstract: Recent studies suggest that gut microbiota composition, abundance and diversity can influence many chronic diseases such as type 2 diabetes. Modulating gut microbiota through targeted nutrition can provide beneficial effects leading to the concept of personalized nutrition for health improvement. In this prospective clinical trial, we evaluated the impact of a microbiome-based targeted personalized diet on hyperglycaemic and hyperlipidaemic individuals. Specifically, BugSpeaks®- a microbiome profile test that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Present clinical trial was conducted to evaluate the safety and impact of BugSpeaks ® microbiome-based personalized dietary regime in hyperglycaemic and hyperlipidaemic individuals, specifically to evaluate the impact of such diet on gut microbiota and other disease related clinical parameters. Please note, that portions of this text were previously published as part of a preprint ( Kallapura et al, 2023 ). The current clinical trial was a randomized, double-blinded, prospective study, initiated with 30 Indian subjects with hyperglycaemia and/or hyperlipidaemia per study design ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Present clinical trial was conducted to evaluate the safety and impact of BugSpeaks ® microbiome-based personalized dietary regime in hyperglycaemic and hyperlipidaemic individuals, specifically to evaluate the impact of such diet on gut microbiota and other disease related clinical parameters. Please note, that portions of this text were previously published as part of a preprint ( Kallapura et al, 2023 ). The current clinical trial was a randomized, double-blinded, prospective study, initiated with 30 Indian subjects with hyperglycaemia and/or hyperlipidaemia per study design ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that a personalized diet based on one’s gut microbiome could significantly help in lowering hyperglycaemia and alleviating its negative effects ( Singh et al, 2017 ; Ben-Yacov et al, 2023 ). A study conducted by the Mayo Clinic Centre for individualized medicine found that a personalized diet based on one’s microbiome (along with genetics, age, and activity level) is a far better way to control one’s blood glucose than cutting carbohydrates and calories ( Mendes-Soares et al, 2019 ; Stanimirovic et al, 2022 ; Kallapura et al, 2023 ). This approach fits into precision medicine paradigm by considering different diet patterns and adopting the best one based on individual microbiota composition to achieve significant adiposity reduction and improve metabolic status ( De Coster et al, 2018 ; Nurk et al, 2022 ; Langmead & Salzberg, 2012 ).…”
Section: Introductionmentioning
confidence: 99%